High-strength short fiber carbon ceramic brake disc and preparation method thereof

By adding thermoplastic resin in the preparation process of the short fiber carbon ceramic brake disc, the resin channel of the network structure is formed, and the closed pore problem caused by cross-linking and curing of thermosetting resins in the prior art is solved, and low porosity and high strength are achieved carbon ceramic brake disc.

CN119490353APending Publication Date: 2025-02-21HUNAN SHIXIN NEW MATERIALS CO LTD
View PDF 0 Cites 6 Cited by

Patent Information

Application Number
CN202411659202.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

When the existing short fiber carbon ceramic brake disc is formed under high temperature and high pressure, the thermosetting resin is prone to cross-linking and curing, resulting in poor fluidity, closed pores, high pore rate and low mechanical properties.

Method used

By adding part of the thermoplastic resin, a resin channel of the network structure is formed, which promotes melting and permeability, reduces the porosity rate, and increases the strength. The specific method includes mixing short carbon fibers, silicon powder, carbon source powder, thermosetting resin powder and thermoplastic resin powder, and carbide and silicone-permeable resin powder after hot pressing.

Benefits of technology

It has achieved low porosity and high strength short fiber carbon ceramic brake discs, which are stronger than foreign short fiber discs and are suitable for automotive or rail transit brakes and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a high-strength short fiber carbon ceramic brake disc and a preparation method thereof, and the preparation method comprises the following steps: carrying out ball milling on silicon powder and carbon powder, mixing with thermosetting resin powder and thermoplastic resin powder, uniformly mixing carbon fiber and a coupling agent, adding the mixed powder, and uniformly mixing again. According to the short fiber carbon ceramic brake disc provided by the invention, the ball-milled silicon powder and carbon powder are uniformly dispersed in the matrix, meanwhile, the thermoplastic resin with good fluidity is added to form a network structure in the matrix, through holes are formed after carbonization, and the high-strength short fiber carbon ceramic brake disc is obtained. Silicon steam can enter in the ceramization process, and the problem that the carbon-ceramic composite material which is high in fiber content and large in thickness and formed at high temperature and high pressure is difficult to infiltrate can be effectively solved. The carbon-ceramic short fiber brake disc prepared by the method is low in aperture ratio and high in impact strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-strength short-fiber carbon-ceramic brake disc and a preparation method thereof, belonging to the technical field of preparation of carbon-ceramic composite materials. Background Art

[0002] In recent years, carbon fiber reinforced carbon-based and silicon carbide ceramic-based composite materials (abbreviated as: carbon ceramics) can be used as a new generation of high-performance friction materials in the braking field and are widely used in the preparation of brake discs due to their excellent properties such as wear resistance, light weight and high temperature resistance.

[0003] The preparation methods of carbon ceramic brake disc preforms can be divided into two categories: one is hot pressing with short fibers, and the other is needle punching with long fibers. Due to the advantages of short fiber hot pressing, such as short preparation cycle and saving raw materials, related carbon ceramic brake disc products have appeared abroad many years ago, and related domestic alternative products have also entered the market. However, since the mechanical properties of short fibers are more lost than those of long fibers, in order to obtain short carbon fiber discs with higher performance, the fiber content in short carbon fiber discs will be relatively higher than that in long fiber discs. However, due to the relatively tight arrangement of fibers, molding under high temperature and high pressure, and the easy cross-linking and curing of thermosetting resins, which leads to poor fluidity, the pores in the preform after carbonization are easy to form closed pores, the brake disc body is thicker, and finally, it is difficult for silicon vapor to penetrate into the carbon-carbon preform during the infiltration process, resulting in a high open porosity and low mechanical properties of the carbon ceramic disc. Summary of the invention

[0004] In view of the problems of the prior art, the first object of the present invention is to provide a method for preparing a high-strength short-fiber carbon-ceramic brake disc. The preparation method of the present invention, by adding a portion of thermoplastic resin, the higher the temperature, the better the fluidity of the thermoplastic powder, forming a resin channel with a network structure, and the thermoplastic resin has a low residual carbon rate. After carbonization, it can form a network of micro-openings, which promotes melt infiltration, so that the opening rate of the product after melt infiltration is low, and the strength is higher than that of foreign short-fiber discs.

[0005] The second object of the present invention is to provide a high-strength short-fiber carbon-ceramic brake disc prepared by the above preparation method.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] The invention discloses a method for preparing a high-strength short-fiber carbon ceramic brake disc, comprising mixing short carbon fibers, silicon powder, carbon source powder, thermosetting resin powder and thermoplastic resin powder to obtain a mixture, then hot-pressing the mixture to obtain a carbon ceramic preform, and then sequentially subjecting the carbon ceramic preform to carbonization treatment and siliconization ceramic treatment to obtain a high-strength short-fiber carbon ceramic brake disc;

[0008] The mixture comprises the following components by mass percentage: 35-65% of short carbon fibers, 2-10% of silicon powder, 1-6% of carbon source powder, 30-45% of thermosetting resin powder, and 1-7% of thermoplastic resin powder.

[0009] The preparation method of the present invention fully grinds inorganic powders by ball milling to promote more uniform dispersion of the powders in carbon fibers. At the same time, by adding part of thermoplastic resin, the higher the temperature, the better the fluidity of the thermoplastic powder, forming a resin channel with a network structure, and the thermoplastic resin has a low residual carbon rate. After carbonization, it can form a network of micro-openings to promote melt infiltration, so that the product after melt infiltration has a low opening rate and higher strength than foreign short fiber disks. However, the amount of thermoplastic resin needs to be controlled within the scope of the present invention. If it is too much, larger pores will be introduced, and the conductive silicon infiltration will not fill the pores, but reduce the performance.

[0010] In a preferred embodiment, the length of the short carbon fibers is 5-35 mm.

[0011] In a preferred solution, the particle size of the silicon powder is ≤20 μm, preferably 3-10 μm.

[0012] In a preferred embodiment, the particle size of the carbon source powder is ≤100 μm, preferably 30-50 μm.

[0013] In a preferred embodiment, the particle size of the thermoplastic resin powder is ≤100 μm, preferably 40-60 μm;

[0014] When the particle size of each raw material is controlled within the above range, the performance of the short fiber carbon ceramic brake disc finally obtained is optimal.

[0015] In a preferred embodiment, the carbon source powder is selected from at least one of asphalt coke powder, graphite powder, petroleum coke powder and carbon black.

[0016] In a preferred embodiment, the thermosetting resin powder is selected from at least one of phenolic resin, furan resin powder and polyimide resin powder. The above preferred resins are all high carbon residue resins.

[0017] In a preferred embodiment, the thermoplastic resin powder is at least one selected from LDPE (low-density polyethylene) powder, PP (polypropylene) powder, EVA (ethylene-vinyl acetate copolymer) powder, and PS (polystyrene) powder.

[0018] In a preferred embodiment, the short carbon fiber, silicon powder and carbon source powder are first modified by a coupling agent, and the amount of the coupling agent added is 0.1-0.5wt% of the mass of the modified substance. By modifying the short carbon fiber, silicon powder and carbon source powder with a silane coupling agent, the dispersibility, bonding and compatibility of the short carbon fiber, silicon powder and carbon source powder in the resin can be improved, so that the performance of the high-strength short fiber carbon ceramic brake disc obtained in the end is optimized.

[0019] Further preferably, the coupling agent is selected from at least one of KH550 (γ-aminopropyltriethoxysilane), KH560 (γ-(2,3-epoxypropoxy)propyltrimethoxysilane), and KH570 (γ-(methacryloyloxy)propyltrimethoxysilane).

[0020] According to a preferred embodiment, the mixed material is obtained by first ball-milling the carbon source powder, silicon powder and coupling agent to obtain modified silicon-carbon powder, then mixing the modified silicon-carbon powder with thermosetting resin powder and thermoplastic resin powder, and finally adding short carbon fibers modified by the coupling agent and mixing.

[0021] The inventors found that by first grinding the inorganic powder through ball milling to obtain modified silicon carbon powder, and then adding the resin powder and then adding the modified short carbon fiber powder in the order of mixing, the powder can be dispersed more evenly in the carbon fiber and the mixture can be more uniform. The final high-strength short fiber carbon ceramic brake disc has the best performance.

[0022] Further preferably, the carbon source powder and silicon powder are mixed to obtain inorganic powder, and the inorganic powder is added to an ethanol solution containing a hydrolyzed coupling agent, ball-milled, and dried to obtain modified silicon-carbon powder.

[0023] More preferably, the method for obtaining the ethanol solution containing the hydrolyzed coupling agent is: adding the coupling agent into water for hydrolysis to obtain the hydrolyzed coupling agent, and then adding ethanol to obtain the hydrolyzed coupling agent.

[0024] The inventors found that the carbon source powder and silicon powder are first mixed, and then an ethanol solution containing a hydrolyzed coupling agent is added and ball-milled together. After the ball milling is fully mixed, the ethanol is allowed to evaporate and dry to obtain modified silicon-carbon powder, which is then mixed with the resin powder. This preferred operation method can achieve the most complete dispersion of the inorganic powder.

[0025] Further preferably, the rotation speed of the ball mill is 100-200 r / min, and the ball milling time is 0.5-2 h.

[0026] Further preferably, the short carbon fibers are mixed with a coupling agent and then dried to obtain short carbon fibers modified by the coupling agent.

[0027] In a preferred embodiment, the mixture comprises the following components by mass percentage: 40-60% short carbon fiber, 3-9% silicon powder, 2-5% carbon source powder, 36-44% thermosetting resin powder, and 2-6% thermoplastic resin powder.

[0028] Further preferably, the mixture comprises the following components by mass percentage: 50-60% short carbon fiber, 3-6% silicon powder, 2-4% carbon source powder, 36-43% thermosetting resin powder, and 2-6% thermoplastic resin powder.

[0029] In a preferred embodiment, the pressure of the hot pressing molding is 0.1-15 MPa, the temperature of the hot pressing molding is 150-210° C., and the time of the hot pressing molding is 30-60 min.

[0030] The carbon ceramic preform is obtained by placing the mixed material in a mold and solidifying the mixed material under the above conditions to shape the mixed material.

[0031] In a preferred embodiment, the temperature of the carbonization treatment is 800°C-950°C, and the holding time is 2-4h; the heating rate is ≤30°C / h, preferably 10°C / h-20°C / h; and the cooling rate is ≤60°C / h, preferably 20°C-40°C / h.

[0032] In a preferred embodiment, the siliconization ceramicization treatment adopts evaporation siliconization, firstly, silicon powder is laid in a carbon ceramic crucible, and then a carbon ceramic pad is placed on the surface of the silicon powder, and then the carbonized carbon ceramic preform is placed on top of the carbon ceramic pad, and the silicon powder and the carbon ceramic preform are separated by the carbon ceramic pad, and the height of the carbon ceramic pad is ≤50mm, preferably 10mm-30mm.

[0033] In the present invention, the preform of the present invention is subjected to evaporation siliconization, so that the overall density of the carbon ceramic disk obtained after the final ceramicization is uniform and the unreacted silicon powder is prevented from adhering to the disk surface as in the embedding method.

[0034] In a preferred embodiment, the amount of silicon powder used in the siliconization ceramic treatment is 1.1-1.3 times the weight of the carbon ceramic preform treated by carbonization. The inventors found that the performance of the carbon ceramic preform is optimal when the amount of silicon powder is controlled within the above range. If the amount of silicon powder is too much, there will not be enough carbon to form silicon carbide in the later stage, which will affect the performance.

[0035] In a preferred embodiment, the temperature of the siliconizing ceramic treatment is 1400°C to 1800°C for 1 to 3 hours. After the siliconizing ceramic treatment is completed, the temperature is lowered and the cooling rate is controlled to be ≤80°C / h, preferably 40°C / h to 70°C / h.

[0036] In actual operation, the short-fiber carbon ceramic brake disc is obtained by fine processing after ceramic treatment.

[0037] The present invention also provides a high-strength short-fiber carbon ceramic brake disc prepared by the above preparation method.

[0038] The high-strength short-fiber carbon ceramic brake disc prepared by the invention has an opening rate of 2.2-4.1% and an impact strength of 9.5-12.3 kJ / m².

[0039] In a further preferred embodiment, the provided high-strength short-fiber carbon ceramic brake disc has an opening rate of 2.2-3.8% and an impact strength of 10.5-12.3 kJ / m².

[0040] The present invention adopts the above technical solution and has the following beneficial effects:

[0041] 1. The present invention provides a method for preparing a high-strength short-fiber carbon ceramic brake disc, which promotes the powder particle size to be smaller and more uniform by ball-milling the non-resin powder and the coupling agent together, and promotes the powder to be evenly dispersed in the resin powder;

[0042] 2. The present invention adds part of thermoplastic resin, so that the higher the temperature, the better the fluidity of the thermoplastic powder, forming a resin channel with a network structure, and the thermoplastic resin has a low residual carbon rate and can form a network of micro-openings after carbonization, thereby promoting melt infiltration.

[0043] 3. The high-strength short-fiber carbon-ceramic brake disc provided by the present invention has a low porosity and high strength. DETAILED DESCRIPTION

[0044] Example 1

[0045] Step 1: Mixing and processing of raw materials

[0046] Silicon powder with a particle size of 3 μm and asphalt coke powder of 30 μm are mixed to obtain non-resin inorganic powder, KH550 coupling agent is added into water for hydrolysis to obtain hydrolyzed coupling agent, and then ethanol is added to obtain an ethanol solution containing the hydrolyzed coupling agent, and the non-resin inorganic powder is added into the ethanol solution containing the hydrolyzed coupling agent, wherein the amount of the coupling agent is 0.3% of the total mass of the silicon powder and the asphalt coke powder, and the mixture is mixed in a ball mill at 100 r / min for 2 hours, and then dried to obtain modified silicon carbon powder, and the improved silicon carbon powder is mixed with phenolic resin powder and 40 μm LDPE powder, and finally 10 mm short carbon fiber modified by 0.3% KH550 is added, and the mixture is continued to be evenly mixed to obtain a mixture, in which, by mass percentage, silicon powder is 9wt%, asphalt coke powder is 5wt%, phenolic resin powder is 44wt%, LDPE powder is 2wt%, and short carbon fiber is 40wt%;

[0047] Step 2: Hot pressing: Add the mixed material into the mold and hot press it on a molding machine at a temperature of 150°C and a pressure of 10 MPa for 2 hours, and then cool it to obtain a preform.

[0048] Step 3: Carbonization. Carbonize the preform at a carbonization temperature of 900°C, a holding time of 3h, a heating rate of 15°C / h, and a cooling rate of 30°C / h;

[0049] Step 4, ceramicization. The carbonized disc is placed in a high-temperature vacuum furnace for high-temperature ceramicization treatment, and the ceramicization is carried out by high-temperature evaporation siliconization. The specific treatment process is as follows: first, silicon powder 1.1 times the weight of the carbonized preform is laid in a carbon ceramic crucible, and then the carbonized coated carbon / carbon composite material disc is placed in the carbon ceramic crucible, and the disc body and the silicon powder interface are separated by a carbon ceramic pad of a certain height to ensure that the height of the disc body and the silicon powder interface is 40mm, the evaporation siliconization temperature is 1600℃, and the time is 2h. After the evaporation siliconization is completed, the cooling rate is controlled at 50℃ / h to obtain a high-strength short fiber carbon ceramic brake disc.

[0050] Example 2

[0051] Step 1: Mixing and processing of raw materials

[0052] Silicon powder with a particle size of 5 μm and petroleum coke powder of 40 μm are mixed to obtain non-resin inorganic powder, KH560 coupling agent is added into water for hydrolysis to obtain hydrolyzed coupling agent, and then ethanol is added to obtain an ethanol solution containing the hydrolyzed coupling agent, and the non-resin inorganic powder is added into the ethanol solution containing the hydrolyzed coupling agent, wherein the amount of the coupling agent is 0.3% of the total mass of the silicon powder and the petroleum coke powder, and the mixture is mixed in a ball mill at 150 r / min for 1 hour, and then dried to obtain modified silicon carbon powder, and the improved silicon carbon powder is mixed with phenolic resin powder and 50 μm PS powder, and finally 20 mm short carbon fiber modified by 0.3% KH560 is added, and the mixture is continued to be evenly mixed to obtain a mixture, in which, by mass percentage, silicon powder is 6wt%, petroleum coke powder is 4wt%, phenolic resin powder is 36wt%, PS powder is 4wt%, and short carbon fiber is 50wt%;

[0053] Step 2: Hot pressing: Add the mixed material into the mold and hot press it on a molding machine at a temperature of 170°C and a pressure of 12MPa for 0.5h, and then cool it to obtain a preform.

[0054] Step 3: Carbonization. Carbonize the preform at a carbonization temperature of 800°C, a holding time of 4 hours, a heating rate of 10°C / h, and a cooling rate of 20°C / h;

[0055] Step 4, ceramicization. The carbonized disc is placed in a high-temperature vacuum furnace for high-temperature ceramicization treatment, and the ceramicization is carried out by high-temperature evaporation siliconization. The specific treatment process is as follows: first, silicon powder 1.2 times the weight of the carbonized preform is laid in a carbon ceramic crucible, and then the carbonized coated carbon / carbon composite material disc is placed in the carbon ceramic crucible, and the disc body and the silicon powder interface are separated by a carbon ceramic pad of a certain height to ensure that the height of the disc body and the silicon powder interface is 50mm, the evaporation siliconization temperature is 1700℃, and the time is 1.5h. After the evaporation siliconization is completed, the cooling rate is controlled at 60℃ / h to obtain a high-strength short fiber carbon ceramic brake disc.

[0056] Example 3

[0057] Step 1: Mixing and processing of raw materials

[0058] Silicon powder with a particle size of 10 μm and graphite powder of 50 μm are mixed to obtain non-resin inorganic powder, KH570 coupling agent is added into water for hydrolysis to obtain hydrolyzed coupling agent, and ethanol is added to obtain an ethanol solution containing the hydrolyzed coupling agent, and the non-resin inorganic powder is added into the ethanol solution containing the hydrolyzed coupling agent, wherein the amount of the coupling agent is 0.3% of the total mass of the silicon powder and the graphite powder, and the mixture is mixed in a ball mill at 200 r / min for 0.5 h, and then dried to obtain modified silicon-carbon powder, and the improved silicon-carbon powder is mixed with phenolic resin powder and 60 μm EVA powder, and finally 20 mm short carbon fiber modified by 0.3% KH570 is added, and the mixture is continued to be evenly mixed to obtain a mixture, in which, by mass percentage, silicon powder is 3wt%, graphite powder is 2wt%, phenolic resin powder is 39wt%, EVA powder is 6wt%, and short carbon fiber is 60wt%;

[0059] Step 2: Hot pressing: Add the mixed material into the mold and hot press it on a molding machine at a temperature of 190°C and a pressure of 15MPa for 0.5h, and then cool it to obtain a preform.

[0060] Step 3: Carbonization. Carbonize the preform at a carbonization temperature of 900°C, a holding time of 2h, a heating rate of 20°C / h, and a cooling rate of 40°C / h;

[0061] Step 4, ceramicization. The carbonized disc is placed in a high-temperature vacuum furnace for high-temperature ceramicization treatment, and the ceramicization is carried out by high-temperature evaporation siliconization. The specific treatment process is as follows: first, silicon powder 1.3 times the weight of the carbonized preform is laid in a carbon ceramic crucible, and then the carbonized coated carbon / carbon composite material disc is placed in the carbon ceramic crucible, and the disc body and the silicon powder interface are separated by a carbon ceramic pad of a certain height to ensure that the height of the disc body and the silicon powder interface is 30mm, the evaporation siliconization temperature is 1800℃, and the time is 1h. After the evaporation siliconization is completed, the cooling rate is controlled to 70℃ / h to obtain a high-strength short fiber carbon ceramic brake disc.

[0062] Example 4

[0063] Step 1: Mixing and processing of raw materials

[0064] Silicon powder with a particle size of 10 μm and carbon black powder with a particle size of 50 μm are mixed to obtain non-resin inorganic powder, KH550 coupling agent is added into water for hydrolysis to obtain a hydrolyzed coupling agent, and then ethanol is added to obtain an ethanol solution containing the hydrolyzed coupling agent, and the non-resin inorganic powder is added into the ethanol solution containing the hydrolyzed coupling agent, wherein the amount of the coupling agent is 0.3% of the total mass of the silicon powder and the carbon black powder, and the mixture is mixed in a ball mill at 200 r / min for 0.5 h, and then dried to obtain modified silicon-carbon powder, and the improved silicon-carbon powder is mixed with phenolic resin powder and 40 μm LDPE powder, and finally 20 mm short carbon fiber modified by 0.3% KH550 is added, and the mixture is continued to be evenly mixed to obtain a mixture, in which, by mass percentage, silicon powder 3wt%, carbon black powder 2wt%, phenolic resin powder 43wt%, LDPE powder 2wt%, and short carbon fiber 60wt%;

[0065] Step 2: Hot pressing: Add the mixed material into the mold and hot press it on a molding machine at a temperature of 210°C and a pressure of 13MPa for 1.5 hours, and obtain a preform after cooling.

[0066] Step 3: Carbonization. Carbonize the preform at a temperature of 850°C, a holding time of 2.5 hours, a heating rate of 10°C / h, and a cooling rate of 20°C / h;

[0067] Step 4, ceramicization. The carbonized disc is placed in a high-temperature vacuum furnace for high-temperature ceramicization treatment, and the ceramicization is carried out by high-temperature evaporation siliconization. The specific treatment process is as follows: first, silicon powder 1.3 times the weight of the carbonized preform is laid in a carbon ceramic crucible, and then the carbonized coated carbon / carbon composite material disc is placed in the carbon ceramic crucible, and the disc body and the silicon powder interface are separated by a carbon ceramic pad of a certain height to ensure that the height of the disc body and the silicon powder interface is 10mm, the evaporation siliconization temperature is 1400℃, and the time is 3h. After the evaporation siliconization is completed, the cooling rate is controlled at 40℃ / h to obtain a high-strength short fiber carbon ceramic brake disc.

[0068] Comparative Example 1

[0069] A high-strength short-fiber carbon ceramic brake disc, the specific preparation steps of which are the same as those of Example 1, except that in Comparative Example 1, the thermoplastic resin added in Example 1 is omitted and the powders are directly mixed without ball milling.

[0070] Comparative Example 2

[0071] A high-strength short-fiber carbon ceramic brake disc, the specific preparation steps of which are the same as those of Example 2, except that in Comparative Example 2, the thermoplastic resin added in Example 2 is omitted and the powders are directly mixed without ball milling.

[0072] Comparative Example 3

[0073] A high-strength short-fiber carbon ceramic brake disc, the specific preparation steps of which are the same as those of Example 3, except that in Comparative Example 3, the thermoplastic resin added in Example 3 is omitted and the powders are directly mixed without ball milling.

[0074] Comparative Example 4

[0075] A high-strength short-fiber carbon ceramic brake disc, the specific preparation steps of which are the same as those of Example 4, except that in Comparative Example 4, the thermoplastic resin added in Example 4 is omitted and the powders are directly mixed without ball milling.

[0076] Comparative Example 5

[0077] A high-strength short-fiber carbon ceramic brake disc, the specific preparation steps of which are the same as those of Example 3, except that the thermoplastic resin added in Example 3 is omitted in Comparative Example 5.

[0078] Comparative Example 6

[0079] A high-strength short-fiber carbon ceramic brake disc, the specific preparation steps of which are the same as those of Example 3, except that in Comparative Example 6, graphite powder and silicon powder are directly mixed without ball milling.

[0080] The high-strength short-fiber carbon ceramic brake disc obtained above was cut into samples and tested for impact strength according to GB / T 14389-1993 and for open porosity using a vacuum method. The test data obtained are shown in Table 1:

[0081]

[0082] From the data obtained in Table 1, it can be seen that: first, the opening rate of the short fiber carbon ceramic brake disc prepared by the present invention is as low as 2.2%, and the impact strength reaches 12.3 kJ / m 2 When the powder is not ball-milled or heated with plastic resin, the impact strength is significantly reduced, and the porosity increases after infiltration, indicating that the ball-milled silicon powder and carbon powder are more conducive to uniform dispersion in the resin. In addition, the thermoplastic resin forms a network of micropores after plasticization and flow under high temperature and high pressure, and leaves through holes after carbonization for silicon vapor to enter and form a path, so the porosity will be reduced and the impact strength will be improved.

[0083] The above content specifically describes a high-strength short-fiber carbon-ceramic brake disc according to the present invention, which can be applied to fields such as automobile or rail transit braking. However, the present invention is not limited to the contents of the above specific implementation methods. Therefore, any improvements, equivalent modifications or replacements based on the technical points of the present invention belong to the scope of protection of the present invention.

Claims

1. A method for preparing a high-strength short-fiber carbon ceramic brake disc, characterized in that: The short carbon fiber, silicon powder, carbon source powder, thermosetting resin powder and thermoplastic resin powder are mixed to obtain a mixture, and then the mixture is hot-pressed to obtain a carbon ceramic preform, and then the carbon ceramic preform is sequentially carbonized and siliconized to obtain a high-strength short-fiber carbon ceramic brake disc; The mixture comprises the following components by mass percentage: 35-65% of short carbon fibers, 2-10% of silicon powder, 1-6% of carbon source powder, 30-45% of thermosetting resin powder, and 1-7% of thermoplastic resin powder.

2. The method for preparing a high-strength short-fiber carbon ceramic brake disc according to claim 1, characterized in that: The length of the short carbon fiber is 5-35 mm; The particle size of the silicon powder is ≤20 μm; The particle size of the carbon source powder is ≤100 μm; The particle size of the thermoplastic resin powder is ≤100 μm; The carbon source powder is selected from at least one of asphalt coke powder, graphite powder, petroleum coke powder and carbon black; The thermosetting resin powder is selected from at least one of phenolic resin powder, furan resin powder and polyimide resin powder; The thermoplastic resin powder is selected from at least one of LDPE powder, PP powder, EVA powder and PS powder.

3. A method for preparing a high-strength short-fiber carbon ceramic brake disc according to claim 1 or 2, characterized in that: The short carbon fibers, silicon powder, and carbon source powder are first modified by a coupling agent, and the amount of the coupling agent added is 0.1-0.5wt% of the mass of the modified substance; The coupling agent is selected from at least one of KH550, KH560 and KH570.

4. A method for preparing a high-strength short-fiber carbon ceramic brake disc according to claim 1 or 2, characterized in that: The process of obtaining the mixture is as follows: firstly, ball-milling the carbon source powder, silicon powder and coupling agent to obtain modified silicon carbon powder, then mixing the modified silicon carbon powder with thermosetting resin powder and thermoplastic resin powder, and finally adding short carbon fibers modified by coupling agent to mix.

5. The method for preparing a high-strength short-fiber carbon ceramic brake disc according to claim 4, characterized in that: The carbon source powder and silicon powder are mixed to obtain inorganic powder, and the inorganic powder is added to an ethanol solution containing a hydrolyzed coupling agent, ball-milled, and dried to obtain modified silicon-carbon powder; The method for obtaining the ethanol solution containing the hydrolyzed coupling agent is as follows: adding the coupling agent into water for hydrolysis to obtain the hydrolyzed coupling agent, and then adding ethanol to obtain the hydrolyzed coupling agent; The ball milling speed is 100-200 r / min, and the ball milling time is 0.5-2 h; The short carbon fibers are mixed with a coupling agent and then dried to obtain short carbon fibers modified by the coupling agent.

6. The method for preparing a high-strength short-fiber carbon ceramic brake disc according to claim 1 or 2, characterized in that: The mixture comprises the following components by mass percentage: 40-60% short carbon fiber, 3-9% silicon powder, 2-5% carbon source powder, 36-44% thermosetting resin powder, and 2-6% thermoplastic resin powder.

7. The method for preparing a high-strength short-fiber carbon ceramic brake disc according to claim 1 or 2, characterized in that: The pressure of the hot pressing molding is 0.1-15 MPa, the temperature of the hot pressing molding is 150-210° C., and the time of the hot pressing molding is 30-60 min.

8. The method for preparing a high-strength short-fiber carbon ceramic brake disc according to claim 1 or 2, characterized in that: The temperature of the carbonization treatment is 800° C.-950° C., the insulation time is 2-4 hours, the heating rate is ≤30° C. / h, and the cooling rate is ≤60° C. / h.

9. The method for preparing a high-strength short-fiber carbon ceramic brake disc according to claim 1 or 2, characterized in that: The siliconization ceramicization treatment adopts evaporation siliconization, firstly, silicon powder is laid in a carbon ceramic crucible, then a carbon ceramic pad is placed on the surface of the silicon powder, and then the carbonized carbon ceramic preform is placed on the top of the carbon ceramic pad, and the silicon powder and the carbon ceramic preform are separated by the carbon ceramic pad, and the height of the carbon ceramic pad is ≤50mm; The amount of silicon powder used in the siliconization ceramic treatment is 1.1-1.3 times the weight of the carbon ceramic preform subjected to carbonization treatment; The temperature of the siliconizing ceramic treatment is 1400° C. to 1800° C., and the time is 1 to 3 hours. After the siliconizing ceramic treatment is completed, the temperature is lowered, and the cooling rate is controlled to be ≤80° C. / h.

10. A high-strength short-fiber carbon-ceramic brake disc prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Molded carbon-ceramic brake disc and preparation method and application thereof

    CN120817814A

  • A molded carbon-ceramic brake disc and a preparation method and application thereof

    CN120817814B

  • Short carbon fiber-based carbon-carbon composite material and preparation method thereof

    CN121159287A

  • Short carbon fiber-based carbon-carbon composite material and method for manufacturing the same

    CN121159287B

  • Short carbon fiber reinforced carbon-ceramic composite material

    CN121342535A